Could Physical Fitness Be Considered as a Protective Social Factor Associated with Bridging the Cognitive Gap Related to School Vulnerability in Adolescents? the Cogni-Action Project - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The first aim was to compare differences between school vulnerability groups, fitness levels, and their combination in adolescent cognitive performance. The second aim was to determine the mediation role of fitness in the association between school vulnerability and cognitive performance. A total of 912 Chilean adolescents aged 10–14 years participated in this study. The school vulnerability index (SVI) assigned by the Chilean Government was categorized into high-, mid-, or low-SVI. Adolescents were classified as fit or unfit according to their global fitness z-score computed from their cardiorespiratory (CRF), muscular (MF), and speed/agility fitness (SAF) adjusted for age and sex. A global cognitive score was estimated through eight tasks based on a neurocognitive battery. Covariance and mediation analyses were performed, adjusted for sex, schools, body mass index, and peak high velocity. Independent analyses showed that the higher SVI, the lower the cognitive performance (F(6,905) = 18.5; p < 0.001). Conversely, fit adolescents presented a higher cognitive performance than their unfit peers (F(5,906) = 8.93; p < 0.001). The combined analysis found cognitive differences between fit and unfit adolescents in both the high-and mid-SVI levels (Cohen’s d = 0.32). No differences were found between fit participants belonging to higher SVI groups and unfit participants belonging to lower SVI groups. Mediation percentages of 9.0%, 5.6%, 7.1%, and 2.8% were observed for the global fitness score, CRF, MF, and SAF, respectively. The mediation effect was significant between low-with mid-high-SVI levels but not between mid-and high-SVI levels. These findings suggest that an adequate physical fitness level should be deemed a protective social factor associated with bridging the cognitive gap linked to school vulnerability in adolescents. This favourable influence seems to be most significant in adolescents belonging to a more adverse social background. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.